2007
DOI: 10.1016/j.joca.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated human mesenchymal stem cells (hMSCs) are highly sensitive to mechanical strain: transcriptionally controlled early osteo-chondrogenic response in vitro

Abstract: Undifferentiated hMSCs are highly sensitive to mechanical strain with a transcriptionally controlled osteo-chondrogenic differentiation response in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 50 publications
(40 reference statements)
7
80
2
Order By: Relevance
“…Some study results have shown that mechanical stimulation can promote osteogenic differentiation of MSCs [Sumanasinghe et al, 2006;Friedl et al, 2007;Hanson et al, 2009]; however, the results of our study showed that the increased osteogenic effect on hASCs under combined stimulation decreased after the 5th day. We do not fully understand the reason why this phenomenon occurred in these cells after long-term mechanical stimulation.…”
Section: Discussioncontrasting
confidence: 88%
“…Some study results have shown that mechanical stimulation can promote osteogenic differentiation of MSCs [Sumanasinghe et al, 2006;Friedl et al, 2007;Hanson et al, 2009]; however, the results of our study showed that the increased osteogenic effect on hASCs under combined stimulation decreased after the 5th day. We do not fully understand the reason why this phenomenon occurred in these cells after long-term mechanical stimulation.…”
Section: Discussioncontrasting
confidence: 88%
“…In fact, although a dilatational component can always be identified for any given loading regime, many tissues of interest experience in vivo stress states that depart very substantially from purely hydrostatic pressure [Potier et al, 2010]. To drive osteogenesis, there are still numerous other forms of mechanical stimulation including but not limited to: substrate strain in uniaxial [Diederichs and van Freiberger, 2009], biaxial or equiaxial directions [Qi et al, 2008;Friedl et al, 2007] and shear stress [Stiehler et al, 2009;Kreke et al, 2008], each having been proven to contribute to new bone formation and maturation. Further research is required to know if estrogen has a synergistic effect with all types of mechanical stimulation that BMSCs encounter, or if its effects are limited to only a few forms of mechanical strain.…”
Section: Discussionmentioning
confidence: 99%
“…FosB is implicated in playing a profibrotic role in that it can induce tenascin-C and CTGF in smooth muscle cells after loading (35). Fos proteins (both c-Fos and FosB), together with Jun, form a complex, AP-1, which is important in cell proliferation and differentiation (8,25), and both genes are important during differentiation of cells with mesenchymal origin such as osteoblasts and chondrocytes (14,15,17,19,36), and might therefore also be involved in tenocyte differentiation. The AP-1 complex also has a binding site in the promoter for collagen type 1 (15), which is the predominating collagen in normal tendons.…”
Section: Fosb and C-fos: Transcription Factors Involved In Proliferatmentioning
confidence: 99%